Baitul Maal Wa Tamwil Sebagai Lembaga Keuangan Mikro Syariah Pemberdaya Ekonomi Umat (Konsep dan Teori) - Solekha, Yasmin Afnan; Murdianah, Alisa Qotrunnada; Lestari, Nofia Sri; Asytuti, Rinda (Velocity: Journal of Sharia Finance and Banking, 2021)
The purpose of the research to dig deeper into the concepts and theories of Baitul Maal Wa Tamwil, because it is based on the fact that occurs in the environment that BMT has shown its success which has been widespread in almost all regions of Indonesia, proven in 2016 reaching 6000 units of BMT and finding good prospects. This type of research is qualitative, supported by data taken in a secondary way using literature study. To support the research, the authors processed the data using Ms. Excel. BMT is a sharia microfinance institution as a non-governmental organization that collects and manages funds according to sharia principles in order to achieve financial and humanitarian economic goals or to achieve mashlahah. BMT does not only focus on financial activities but also social virtue activities. BMT refers to the authoritative source of Islam, Law no. 25 1992 concerning cooperatives and the DSN-MUI fatwa. The source of finance comes from customers and the results of operating income. Customer funds are then managed using sharia financing and contracts, the profits are known as profit sharing. BMT must always conduct evaluations so that the operational system and its resources are better and continue to disseminate information to the community.